Assessment of ameliorative effects of Moringa oleifera Lam. on epididymal dysfunctions and fertility in streptozotocin–induced diabetic rats - Ram Niwas Jangir; Gyan Chand Jain (Asian Pacific Journal of Reproduction)
Objective: To assess the protective effects of 70% ethanolic extract of Moringa (M.) oleifera leaves on fertility and epididymal dysfunctions in diabetic rats. Methods: Thirty-six male Wistar rats were divided into six groups, each with six rats. Group I was the normal control group receiving vehicle (0.5 mL of distilled water/rat/day) orally; group II, III, IV, V and VI were injected intraperitoneally with 60 mg/kg of streptozotocin once to induce type I diabetes. Then, the diabetic rats in group II receiving vehicle (0.5 mL of distilled water /rat/day) orally; the diabetic rats in groups III, IV and V were orally treated with M. oleifera leaf extract at dose of 100, 250, and 500 mg/kg body weight (b.wt.)/day, respectively; the diabetic rats in group VI were administrated with reference drug glibenclamide (5 mg/kg b.wt./day). The treatment lasted for 60 days. Sperm parameters (sperm count, motility and viability), fertility index, litter size, lipid peroxidation and antioxidative defense markers (i.e. superoxide dismutase, catalase, glutathione, and ascorbic acid) in the epididymal tissue were determined. Histopathological changes in epididymis were also evaluated. Results: Administration of different doses of M. oleifera leaf extract in diabetic rats induced a remarkable dose dependent improvement in sperm parameters, fertility index, litter size, epididymal antioxidant status and also restored histopathological changes as compared to the diabetic control group. These findings were comparable with reference drug. Conclusions: M. oleifera leaf extract possesses significant antioxidant activities as well as beneficial effects on epididymal dysfunctions in diabetic male rats.